Mathematical modelling on special diet for myopia patients - Kwek, Yan Ping; Sufahani, Suliadi (International Journal of Multidisciplinary Research and Development, 2018)
Due to the number of myopia patients keep increasing, a special diet is required to reduce or even prevent myopia disease. However, there is no research about the special menu planning for myopia patients. A menu planning should considered all the necessity and confinement of individual. The mathematical modelling can be used in menu planning to satisfy all the nutrient requirements of a person with the lowest price. This paper indicates various types of mathematical optimizing techniques are used in operation research. The myopia patients can practice special diet that designed by optimizing mathematical technique.